The Effectiveness of Canva as a Digital Writing Tool in Improving Descriptive Writing Skill of the Eleventh-Grade Students at Senior High School - Nadya; Konder Manurung; Sukmawati Sadilia (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
The purpose of this study is to investigate the efficacy of using Canva as a digital writing tool in enhancing students’ descriptive writing. Contrary to the other studies, the current research focuses on examining Canva’s effectiveness as a digital writing tool to assist students in developing their descriptive writing skill. It should be stated that the main motivation for conducting the current study is the poor ability of students to organize ideas, lack of vocabulary, and lack of interest in writing descriptive texts. To conduct the research, researchers followed the quasi-experimental design, including pre-test and post-test with a control group. The participants of this study comprised of 31 eleventh-grade students studying at MAN 1 Palu, whereof 16 of them were placed in the experimental group while the other 15 students formed the control group. In order to perform the experiment, the researchers designed several activities during six sessions. Descriptive text writing test was employed as the data collection technique, which was later analysed using descriptive statistics and aided by the Independent Samples t-test in conjunction with the use of SPSS. Consequently, the following findings emerged as a result. The mean score for the experimental group was raised from 52.00 in the pre-test to 68.81 in the post-test. For the control group, the score increased from 49.40 to 56.60. From the results of the Independent Samples t-test, there was a significant difference between the two groups (p = 0.002 < 0.05). Additionally, the effect size showed a large effect (Cohen’s d = 1.236), signifying practical importance.